New record of a Comet grass - Perotis hordeiformis Nees from traditional rubber plantation, southern Tamil Nadu, India - Rijuraj, M. P.; Joseph, M. D. (Journal of Plantation Crops, 2026)
Perotis hordeiformis Nees, earlier known only from three States of India-Rajasthan, Uttarakhand and West Bengal, has been recorded for the first time in State Tamil Nadu form traditional rubber plantation of Kanyakumari district. This discovery expands the known geographic distribution of the species, providing new insights into its distributional range. A comprehensive description, distribution map and photographs of the species, also key to Indian Perotis is included.